Ethnic differences in physical pain sensitivity: Role of acculturation - Chan, M.; Hamamura, Takeshi; Janschewitz, K. (Elsevier Science, 2013)
Although research suggests that Asian Americans are more reactive to physical pain than European Americans, some evidence suggests that the observed differences in ethnicity may actually reflect Asian Americans’ differing levels of acculturation. Two studies were conducted to test this hypothesis. In Study 1, first- and second-generation Asian Americans and European Americans took part in a cold pressor task.Evidence of heightened pain responses was found only among first-generation Asian Americans. Study 2 further controlled for ethnicity and replicated this pattern in finding heightened pain reactions among mainland Chinese students in Hong Kong relative to Hong Kong Chinese students. These findings suggest a role for acculturation in accounting for ethnic differences in physical pain sensitivity.